Modeling and comparative analysis of sustainable cotton rope confinement: Full vs. STrip wrapping for enhanced concrete strength and ductility - Saingam, Panumas; Gadagamma, Chaitanya Krishna; Hussain, Qudeer; Hlaing, Hnin Hnin; Suwannatrai, Rawirot; Qureshi, Muhammad Irshad; Khan, Kaffayatullah; Ejaz, Ali (My University, 2025)
The rise of natural FRPs as ecological alternatives to synthetic ones has highlighted the need for studies on partial confinement using cotton ropes, which offer cost-effective, low-carbon solutions with high rupture strain. Unlike full confinement, partial confinement through cotton rope strips can efficiently strengthen deteriorated concrete sections with reduced material usage. Despite possessing several advantages, the partial confinement by cotton on concrete has not been investigated. This study addresses the gap by investigating the performance of cotton rope strips and developing analytical models to predict their structural impact. This study tested cylindrical concrete specimens of two strengths, strengthened with cotton rope in either complete wrapping (Group 1) or strip wrapping (Group 2). Each group was further divided by concrete strength and included one unstrengthened specimen, and three strengthened with one, two, or three layers of cotton rope. Experimental results revealed that cotton rope wraps effectively confined the concrete, enhancing load-bearing capacity and improving ultimate compressive strength by 9.97–152.10 % and ultimate strain by 188.00 % to 1488.89 %. The compressive stress vs. strain behavior exhibited an initial stiff elastic ascent followed by a parabolic transition. The second branch of the response, either ascending or descending, was significantly improved with an increased confinement ratio. Type-I failure was characterized by an ascending second branch in the compressive stress vs. strain curve, while Type-II failure exhibited a descending second branch. Four specimens demonstrated Type-I failure (L-2F, L-3F, H-3F, and L-3S), predominantly in full configurations and with lower unconfined compressive strength. The modulus of the second branch improved with an increased confinement ratio, transitioning from Type-II to Type-I failure near a ratio of approximately 0.50. Regression analysis provided equations of various key points along the compressive response with R² values greater than 0.90, highlighting a strong dependence on the confinement ratio. The Popovics model effectively predicted the first part of the compressive response, with predicted curves closely matching experimental results.
Keywords: Concrete; Confinement; Confinement ratio; Cotton; Predictions; Regression